2011
DOI: 10.1007/s00044-010-9547-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lipophilic parameter (log P) on the anti-parasitic activity of imidazo[1,2-a]pyridine derivatives

Abstract: A number of imidazo[1,2-a]pyridine derivatives were selected and investigated in relation to antiparasitic (Trichomonas vaginalis) activity. After treatment with derivatives, biological activity was assessed by determination of the in vitro viability of cell cultures, using alamar blue as a metabolic indicator. A good correlation was found between the anti-parasitic activity and the partition coefficient log P determined experimentally on the tested compounds, which explained up to 84% of the measured activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The high affinity of 7 was expected since the carboxylic group is a common feature in classic NSAIDs, whereas the electro‐withdrawing nitro functionality in compound 1 seems a good alternative. The biological activities of the cyclohexyl or aminocyclohexyl functional groups in compound 15 have been previously evaluated as part of other heterocyclic compounds . Thus, it can be concluded that the electro‐withdrawing, acidic, and volumetric functional groups will favor COX‐1/2 binding.…”
Section: Resultsmentioning
confidence: 99%
“…The high affinity of 7 was expected since the carboxylic group is a common feature in classic NSAIDs, whereas the electro‐withdrawing nitro functionality in compound 1 seems a good alternative. The biological activities of the cyclohexyl or aminocyclohexyl functional groups in compound 15 have been previously evaluated as part of other heterocyclic compounds . Thus, it can be concluded that the electro‐withdrawing, acidic, and volumetric functional groups will favor COX‐1/2 binding.…”
Section: Resultsmentioning
confidence: 99%
“…The pest control potency of imidazopyridine was assessed using Trichomonas Vaginalis. GT3 was a highly pathogenic strain isolated in the city of Guanajuato, Mexico in 2012 [94]. Margarita Lopez-Martinez et al showed that most of the synthezisedcompounds got antiparasitic activity after 24 h of treatment.…”
Section: H Imidazo[12-a]pyridine As a Pest Controlmentioning
confidence: 99%
“…The functionalized heterocycles demonstrate a significant biological activities in medicinal chemistry . Recently, the fused heterocyclic system functionalized imidazo[1,2‐a]pyridine has been recognized as an important pharmacophore, some of them were investigated as lipophilic parameter (log P) on the anti‐parasitic activity, docking simulations and anti‐inflammatory activity evaluation, of 2‐(N‐alkyl)amino‐3‐nitroimidazo[1,2‐a]pyridines, antiproliferative activity against melanoma cells, protein kinase inhibitors, antimicrobial activity and synergistic effects of novel organoselenium based imidazo[1,2‐a]pyridine compounds . The potential antipsychotic activity of fluorinated imidazo[1,2‐a]pyridine derivatives were also recognized as colon cancer cell lines HT‐29, and Caco‐2, antimicrobial screening, urease inhibition of 5‐substituted‐8‐methyl‐2H‐pyrido[1,2‐a]pyrimidine‐2, 4(3H)‐diones, and anticonvulsant studies of 6‐bromoimidazo[1,2‐a]pyridine‐2‐carbohydrazide derivatives …”
Section: Introductionmentioning
confidence: 99%